Encoding many channels on the same frequency using orbital angular momentum multiplexing - De Silva, Pasan Bhashitha (2018)
The contribution of this dissertation is to analyse and propose the methodology for encoding many transmission channels in the same frequency using Orbital Angular Momentum (OAM) of a radio wave. First part of this dissertation includes the theoretical formulation of twisted radio wave transmission using a circular array of half wave dipole antennas. This theoretical analysis includes deciding the optimum number of antennas required to transmit multiple OAM modes, with minimum tolerable magnitude and phase errors. Then experimental verification of twisted radio wave using a VNA based virtual circular array of dipole antennas is carried out in the anechoic chamber and compared with the simulation results. By observing the magnitude and phase patterns generated by different OAM modes of twisted radio wave, a real time OAM multiplexing transceiver system has been designed to transmit two OAM modes simultaneously and receive them independently. The system has been designed using National Instrument (NI) based Vector Signal Transceiver (VST) model PXIe-5644. In addition to OAM multiplexing, it has also been shown both theoretically and experimentally that twisted radio wave transceiver system has the capability of enhancing the Line of Sight (LOS) twisted radio wave signal and mitigating multipath components in indoor environments. Hence the designed system has the capability of providing a stable point-to-point communication link based on twisted radio wave. The capability of the designed system to. transmit multiple channels in the same frequency and providing a point-to-point stable transmission link in indoor multipath environments has been presented experimentally in comparisons with respective simulations in different indoor environments.